First detection of the S989P+V1016G+D1763Y haplotype and expansion of voltage-gated sodium channel mutations in Aedes aegypti in Taiwan in 2016-2023. - Han-Hsuan Chung; Hwa-Jen Teng; Chin-Gi Huang; I-Jung Tsai; Hung-Jui Chen; Osamu Komagata; Shinji Kasai; Kun-Hsien Tsai; Shiu-Ling Chen (PLoS Neglected Tropical Diseases)
Background Aedes aegypti transmits various arthropod-borne diseases such as dengue, posing a significant burden to public health in tropical and subtropical regions. Pyrethroid-based control strategies are effective in managing this vector; however, the development of insecticide resistance has hindered these efforts. Hence, long-term monitoring of insecticide resistance in mosquito populations is crucial for effective vector and disease control. Methodology/principal findings In this study, we identified insecticide resistance due to a voltage-gated sodium channel (vgsc) mutation in Ae. aegypti in Taiwan between 2016 and 2023. In total, 1,761 field-caught Ae. aegypti samples from Tainan, Kaohsiung, and Pingtung were genotyped. The frequencies of S989P, V1016G, T1520I, F1534C, and D1763Y amino acid variants increased over the surveillance period. A T1520I mutation was detected for the first time and has since rapidly spread throughout Taiwan. The triple-mutant haplotype PGTFY was first documented in Ae. aegypti. Moreover, the unmutated haplotype vanished in Taiwan, suggesting that the vgsc mutations were fixed in local populations of Ae. aegypti. Five resistance-associated genotypes, SVTCD/SVTCD, SGTFY/PGTFD, SVTCD/SGTFY, PGTFD/PGTFD, and SVTCD/PGTFD, exhibited an increased frequency and accounted for 76% of the total field population. We also detected the resistant genotype SVICD/PGTFD, and its frequency increased 13-fold in the field between 2016 and 2023. Moreover, we also observed that mutations differed geographically, with S989P mainly found in Kaohsiung and V1016G in Kaohsiung and Pingtung. The frequency of T1520I was noticeably higher in Kaohsiung, and D1763Y occurred mainly in Tainan. Conclusions/significance The emergence and expansion of mutations along with the disappearance of wild-type mosquitoes in Taiwan underscores the threat of resistance and difficulty of mosquito control in Taiwan as well as globally. This study determined the insecticide resistance status of Ae. aegypti in Taiwan, and the findings will be helpful for resistance monitoring in areas where pyrethroids are used to control Ae. aegypti.